The Creed of Nicaea: The Divine Sacrifice of Jesus, the Confession of the God of Life and the Resistance against the Power of Death - Appel, Kurt (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
This article examines the soteriological implications of the Nicene Creed, emphasizing its compatibility with biblical monotheism and its significance for interreligious dialogue. Through a detailed analysis of its biblical roots, the article elucidates how the Creed articulates consubstantiality of Jesus Christ with the Father by translating biblical motifs into theological language. It is argued that the Nicene formulation not only preserves the unity of the one God but also provides a framework for contemporary theological reflection, particularly in relation to the oneness of JHWH, the name of God and Jesus as its decisive verbalization. For a profound interpretation of consubstantiality, the article contrasts the Christian understanding of sacrifice, centered on the divine sacrifice of Jesus as gift of life and opposition to the annihilating power of death, with pagan sacrificial systems, that sacrifice man to serve death. This highlights the Bible’s rejection of imperial power and affirmation of life.